Genetic Variants of the Brain-Derived Neurotrophic Factor and Metabolic Indices in Veterans With Posttraumatic Stress Disorder - Tudor, Lucija; Konjevod, Marcela; Nikolac Perkovic, Matea; Svob Strac, Dubravka; Nedic Erjavec, Gordana; Uzun, Suzana; Kozumplik, Oliver; Sagud, Marina; Kovacic Petrovic, Zrnka; Pivac, Nela (Frontiers in Psychiatry, 2018)
Posttraumatic stress disorder (PTSD) is a trauma and stressor related disorder that may develop after traumatic experience. The vulnerability or resilience to develop PTSD differs among traumatized subjects, and its molecular underpinning is still not clear. Brain-derived neurotrophic factor (BDNF) modulates neuronal survival, differentiation, synapse formation, brain plasticity and neurotransmission, but also response to stress and stress related behaviours. BDNF also regulates food intake, weight control, energy and glucose expenditure and homeostasis. Plasma BDNF levels and a functional BDNF Val66Met (rs6265) polymorphism were reported to be associated with PTSD, but also with increased body mass index (BMI) and dyslipidaemia in healthy subjects and patients with cardio-metabolic diseases, but these results are controversial. The other frequently studied BDNF polymorphism, C270T (rs56164415), has been associated with the development of different neuropsychiatric symptoms/disorders. As far as we are aware, there are no data on the association of BDNF rs6265 and rs56164415 polymorphisms with metabolic indices in PTSD. Given the alarmingly high rates of both obesity and dyslipidaemia in PTSD, the aim of this study was to elucidate the association of BDNF rs6265 and rs56164415 polymorphisms with BMI and lipid levels in veterans with PTSD. We hypothesized that BDNF variants contribute to susceptibility to metabolic disturbances in PTSD. The study included 333 Caucasian males with combat related PTSD, diagnosed according to DSM-5 criteria. Genotyping of the BDNF rs6265 and rs56164415 polymorphisms was performed using real-time PCR method. Results were analysed using Kruskal-Wallis ANOVA, Mann-Whitney test and stepwise multiple linear regression, with p value corrected to 0.005. The results showed that BDNF rs6265 polymorphism was not significantly associated with BMI (p=0.795), total cholesterol (p=0.696), LDL-cholesterol (p=0.441), HDL-cholesterol (p=0.604) or triglycerides (p=0.697). In contrast, BDNF rs56164415 polymorphism was significantly associated with HDL-cholesterol in veterans with PTSD. Higher plasma HDL values were found in the CT genotype carriers (H=15.521; df=2; p0.001) compared to other genotype carriers, and in T allele carriers (U=9218.00; p0.001) compared to CC homozygotes. These results, demonstrating that the presence of T alleles could be related to higher HDL-cholesterol levels, suggested the association between BDNF rs56164415 polymorphism and metabolic indices in veterans with PTSD.